DAMPAK FLY OVER MANAHAN TERHADAP ARUS LALU LINTAS - Susi Febriana; Nurul Hidayati; Gotot Slamet; Ika Setiyaningsih (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2019)
Surakarta has several locations prone to congestion due to at grade highway-railway crossing, one of which is in the Manahan area. The solution made by the government to overcome this problem was to build the Fly Over. Nevertheless, this condition affects the surrounding traffic condition, such as on Slamet Riyadi Street. This study aims to determine the characteristics of the traffic, and the existing performance of the road, then to compare it with the previous road performance. The primary data used are the existing condition of geometric, side frictions, volume and travel time which is then analyzed using IHCM 1997. The results show that ??during morning peak hour is obtained a volume of 1827.7 pcu per hour with the averages speed is 38.25 km per hour. The road performance expressed by the degree of saturation is obtained at 0.38. This value is smaller than before the change. This shows that the performance after the Fly Over is better than before. Nevertheless, both performances are still categorized in good condition.